Effect of different application rates of pesticides to groundnut (Arachis hypogaea L.) Soils of Ananatapuramu District - P., Ramanamma; K., Swetha; V., Rangaswamy (International Journal of Scientific Research in Biological Sciences, 2021)
This study was undertaken to determine the effect of pesticides, on Amylase activity in two groundnut (Arachis hypogaea L.) soils. The effect of the pesticides were assessed over a period of 10, 20, 30 and 40 days for Amylase activity. Soil samples (red sandy loam and black clay soils) collected from groundnut (Arachis hypogaea L.) cultivated fields of Ananatapuramu District of Andhra Pradesh, India were treated with pesticides at different concentrations i.e. 10, 25, 50, 75 and 100 ppm, which are equivalent to field application rates (1.0, 2.5, 5.0, 7.5 and 10.0 kg ha-1) in the laboratory. The activity of Amylase was significantly more treated with pesticides at levels of 2.5 kg ha-1 in black and red soils respectively at 24 and 72hrs. But at higher concentrations of 7.5 and 10.0 kg ha-1 respectively, pesticides were toxic to amylase activity. The activity of amylase was drastically decreased with increasing period of incubation up to 40 days.